Genome Announcement: Draft Genome Assembly of Heterodera humuli Generated Using Long-Read Sequencing - Núñez-Rodríguez Lester A.; Wram Catherine L.; Hesse Cedar; Zasada Inga A. (Journal of Nematology)
The hop cyst nematode, Heterodera humuli, is the most common plant-parasitic nematode associated with hop worldwide. This study reports the draft genome of H. humuli generated on the PacBio Sequel IIe System with the ultra-low DNA input HiFi sequencing method, and the corresponding genome annotation. This genome resource will help further studies on H. humuli and other cyst nematodes.